Understanding the Genetic Makeup of Linux Device Drivers - TSCHUDIN, Peter Senna (Institutional Knowledge at Singapore Management University, 2013)
Attempts have been made to understand driver development in terms of code clones. In this paper, we propose an alternate view, based on the metaphor of a gene. Guided by this metaphor, we study the structure of Linux 3.10 ethernet platform driver probe functions.